Assembly and comparative analysis of the complete mitochondrial genome of red raspberry (Rubus idaeus L.) revealing repeat-mediated recombination and gene transfer - Huajie Zhang; Minghui Yan; Lijuan Li; Zhuo Jiang; Ye Xiong; Yusheng Wang; Caleb Onoja Akogwu; Olutayo Mary Tolulope; Hao Zhou; Yanxia Sun; Hengchang Wang (BMC Plant Biology)
Abstract Background Red raspberry (Rubus idaeus L.) is a renowned fruit plant with significant medicinal value. Its nuclear genome and chloroplast genome (plastome) have been reported, while there is a lack of genetic information on its mitogenome. We sequenced and assembled the complete mitogenome of R. idaeus, and conducted a series of genetic investigations comparing it with the nuclear and chloroplast genomes, so as to better gain a comprehensive understanding of the species’ genetic background. Results The mitogenome is represented by one circular chromosome of 438,947 bp. Twenty-four core genes, nine variable genes, 26 tRNAs, and three rRNAs were annotated. A total of 52 SSRs and 38 tandem repeat sequences were identified. 533 pairs of dispersed repeats were detected, among which three pairs were found to have mediated the homologous recombination, resulting in one major conformation and seven minor conformations. Furthermore, 52 homologous sequences between the mitogenome and plastome were identified, including six complete protein-coding genes and 12 tRNA genes. We also detected 828 homologous fragments between the nuclear genome and mitogenome, including one trnM-CAU gene. Conclusions In this study, we presented the mitogenome of R. idaeus for the first time based on data obtained from Illumina and Oxford Nanopore sequencing platforms. Key characteristics of the mitogenome were examined, including its gene composition, repetitive elements, and homologous DNA fragments. Additionally, we identified multiple recombination events in the mitogenome mediated by repetitive sequences The high-quality and well-annotated mitogenome for the known fruit red raspberry will provide essential genetic information for species classification, evolution analysis, and even genetic improvement in Rubus in the future.